Design and innovation to enhance SMEs new product development - Nur Haizal Mat Yaakob@Ariffin; Universiti Teknologi Mara . Faculty of Art and Design (2017)
Design and innovation playa very significant role in producing innovative and high added value of products through new product development (NPD) process thus can enhance the SMEs' performance. However, the numbers of SMEs manufacturing involved in developing product by utilizing design and innovation is not at a good level. In order to understand how de ign and innovation has been practiced in the SMEs in developing new product, this research combined quantitative and qualitative data collection methods including a literature review, questionnaire survey and interview. Interviews include open ended and semi-structured interviews with staff who directly involved in the process of NPD, questionnaire surveys helped to provide background and validate findings from the secondary sources. Both data for quantitative and qualitative were collected through industrial de igners, marketers and decision makers. The study has focused on SME in furniture, consumer durable product and automotive industries. The interviews focused on six issues (,Parties involve', 'Implementation', 'Management', 'Performance achievement', and 'Quality'. An overall finding shows that even though most SMEs know the importance of design and innovation as their sources of competitive advantages, however they are not fully engaged with the activity as they feel it would increase their operation costs. Additionally, they are more focused on generating profits in a short time rather than doing something risky. Besides that, there are differences in terms of the implementation stages in new product development process (NPD). Most of furniture produced by SMEs usually carry out Prototyping and use existing design as their references to produce new furniture design. Furthermore, the nature of the industry itself does not really encourage them to come out with their own design. By contrast, SMEs in con umer durable product and automotive sector do implementing the whole stages of the NPD. The involvement of specific parties or expertise is important to ensure the successful of the NPD process. So, based on the result of this study, it can be concluded that SMEs should actively be involved with the design and innovation process, particularly through the NPD because it positively contributes to enhance their performance. Due to that, commitment from all parties especially top management or decision makers is important since it will motivate others like marketers, designers, engineers and also other workers in the company to work together as a good team in developing new product. The managerial aspect is also very crucial to ensure the success of the NPD process. Therefore, SMEs has operated
in rapidly changing environment in which design and innovation should be used as the key factor to enhance their economic Success. They must actively move a step forward
by properly doing it in-house or by outsourcing from the expertise. This is important
to realize our leader's mission: Malaysia's innovations.
Thesis (Degree of Doctor of Philosophy) - Universiti Teknologi Mara, 2017
Includes bibliographical references (p. 246-289)
Keywords: Universiti Teknologi Mara -- Faculty of Art and Design -- Dissertations; Product design; Product design -- Planning; Product design -- Technological innovations